已知函数fn(x)=
(Ⅰ)求Sn; (Ⅱ)若对任意的n∈N*,总存在x∈R+使
(Ⅲ)比较
|
(Ⅰ)fn′(x)=
,(2分)-ln(x+n)+n+1 (x+n)2
令fn′(x)>0,则x<en+1-n.
∴fn(x)在(-n,en+1-n)上递增,在(en+1-n,+∞)上递减.(4分)
∴当x=en+1-n时,fn(x)max=fn(en+1-n)=
+1 en+1
(5分)1 n(n+1)
即an=
+1 en+1
,1 n(n+1)
则Sn=
+en-1 en+2-en+1
.(6分)n n+1
(Ⅱ)∵n≥1,∴en+1递增,n(n+1)递增,
∴an=
+1 en+1
递减.1 n(n+1)
∴0<an≤a1=
+1 e2
,1 2
即an∈(0,
+1 e2
](8分)1 2
令g(x)=
+a,则g′(x)=x ex-1
,1-x ex-1
∴g(x)在(0,1)上递增,在(1,+∞)上递减.
当x→0时,
→0;x ex-1
当x→+∞时,
>0;x ex-1
又g(1)=1+a,
∴g(x)∈(a,1+a](10分)
由已知得,(a,1+a]⊇(0,
+1 e2
],1 2
∴
∴a≤0
+1 e2
≤1+a1 2
-1 e2
≤a≤0(11分)1 2
(Ⅲ)
+fn(en)-an1 en+1+e•n
=
+1 en+1+e•n
+ln(en+n)-n en+n
-1 n(n+1)
-1 en+1 1 n(n+1)
=
+1 e(en+n)
ln1 en+n
-en+n en 1 en+1
=
(1 en+n
+ln1 e
-en+n en 1 e
)(12分)en+n en
令t=
,en+n en
∵g(x)=
(x≥1),g′(x)=ex+x ex
≤0∴g(x)在[1,+∞)上递减.1-x ex
∴1<g(x)≤1+
,1 e
即t∈(1,1+
](13分)1 e
又r(t)=
+lnt-1 e
t,r′(t)=1 e
-1 t
>0∴r(t)>r(1)=0(14分)1 e
∴
(1 en+n
+ln1 e
-en+n en 1 e
)>0en+n en
∴
+fn(en)>an(15分)1 en+1+e•n